Multimedia instructional materials in teaching basic science concepts for students with hearing impairment - Ugochi Nnenna Ndoh; Mary Ashelo Umbugadu (Goodwood Publishing, 2024)
Purpose: The purpose of this study was to examine the impact of multimedia instructional materials in teaching basic science concepts to students with hearing impairment in Nasarawa State. Methodology/approach: The study used a questionnaire to collect responses from respondents. Sixty (60) students were sampled, and simple percentages, means, and standard deviations were used to analyze the findings. Results/Findings: The findings of the study showed that the use of multimedia is important, as many students with hearing impairment did understand what was taught. In addition, multimedia instructional materials aid student retention during examinations. When multimedia materials were used by the students, they were motivated by their use during science lessons. The respondents’ responses also identified many challenges facing the use of multimedia instructional materials in teaching science. Limitations: The scope of this study must be expanded. Contribution: This study shows the impact of multimedia instructional materials in teaching basic science concepts and effective modern methods for students with hearing impairment. Recommendations: The study recommends that students at all levels of education should be given adequate information on the impact of multimedia instructional materials on the teaching of basic science to learners with hearing impairment in order to promote the interest of these students in science subjects.